(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Systemic lupus erythematosus is a chronic autoimmune disease which may affect every organ in the body. According to reports, 5% to 11% of SLE patients experience inflammatory myositis that affects the proximal muscles. This condition can appear at any point throughout the disease's progression. Additionally, it may develop as a result of internal cancers. Methodology: We hereby report a 57 year SLE patient, on hydroxychloroquine who presented with neck muscle weakness for one week duration. Imaging revealed myositis in the neck region and autoimmune profile positive ANA, Anti SSN, Ro 52, and dsDNA and low serum complement levels. Other investigations were within normal limits. Results: Hence the diagnosis of inflammatory polymyositis secondary to systemic lupus erythematosus was made and patinets was managed successfully with steroids, hydroxychloroquine and immunosuppressants. Conclusion: Proximal muscle weakness in SLE may be due to a drug-related myopathy secondary to corticosteroid, statin medications use or antimalarial, concurrent hypothyroidism or secondary to SLE. Thus prompt evaluation can be life saving to the patient.